2015
DOI: 10.1007/s12671-015-0463-y
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Evaluation of Student Learning and Skills Use in a School-Based Mindfulness and Yoga Program

Abstract: Previous studies on school-based mindfulness and yoga programs have focused primarily on quantitative measurement of program outcomes. This study used qualitative data to investigate program content and skills that students remembered and applied in their daily lives. Data were gathered following a 16-week mindfulness and yoga intervention delivered at three urban schools by a community non-profit organization. We conducted focus groups and interviews with nine classroom teachers who did not participate in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 27 publications
7
39
0
1
Order By: Relevance
“…The results of the present study are, for the most part, consistent with prior qualitative research on yoga in schools (Case-Smith et al, 2010; Conboy et al., 2013; Dariotis et al, 2016a; Dariotis et al, 2016b; Finnan, 2015; Miller et al, 2014; Wang & Hagins, 2016). For example, many students in the present study reported that they found yoga helpful for enhancing relaxation and reducing stress, a finding that is similar to other qualitative studies of school-based yoga (Conboy et al, 2013; Case-Smith et al, 2010; Dariotis et al, 2016a; Dariotis et al, 2016b; Miller et al, 2014; Wang & Hagins, 2016).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The results of the present study are, for the most part, consistent with prior qualitative research on yoga in schools (Case-Smith et al, 2010; Conboy et al., 2013; Dariotis et al, 2016a; Dariotis et al, 2016b; Finnan, 2015; Miller et al, 2014; Wang & Hagins, 2016). For example, many students in the present study reported that they found yoga helpful for enhancing relaxation and reducing stress, a finding that is similar to other qualitative studies of school-based yoga (Conboy et al, 2013; Case-Smith et al, 2010; Dariotis et al, 2016a; Dariotis et al, 2016b; Miller et al, 2014; Wang & Hagins, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…To our knowledge, 14 qualitative studies of youth-based mind-body interventions have been conducted, all of which have generally shown positive participant-reported outcomes for children, adolescents, and young adults (Case-Smith, Shupe Sines, & Klatt, 2010; Conboy, Noggle, Frey, Kudesia, & Khalsa, 2013; Dariotis et al., 2016a; Dariotis et al, 2016b; Dariotis et al, 2017; Finnan, 2015; Miller et al, 2014; Rosaen & Benn, 2006; Sibinga et al, 2011; Sibinga, Perry-Parrish, Thorpe, Mika, & Ellen, 2014; Tharaldsen, 2012; Wall, 2005; Wang & Hagins, 2016; Wisner, 2014). However, it is important to note that only 12 of the 14 aforementioned studies were conducted within school settings, and only eight evaluated yoga interventions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is an extension of previous qualitative program findings related to mindful yoga skills learned and program implementation. 35,36 Data from youth focus groups were analyzed to explore the experiences of fifth and sixth grade urban students who attended a 16-week school-based mindfulness and yoga program. We explored the following domains: (1) how youth conceptualized stress; (2) common sources of stress identified by youth; and (3) youths’ perceptions of shifts in their ability to cope with stress after participating in the school-based mindfulness and yoga program.…”
Section: Introductionmentioning
confidence: 99%